Dynamic games for resource allocation in metaverse services and architectures - Han, Yue (Nanyang Technological University, 2023)
The Metaverse is an interoperable platform, hosting various virtual sub-worlds, each of which is operated by a virtual service provider (VSP) to provide various types of virtual services, such as virtual sightseeing, virtual driver training, etc. There are many latency-sensitive and computation-intensive (LSCI) tasks in the Metaverse, such as scene rendering, 3D reconstruction, multi-user interactions, and data analytics based on Artificial Intelligence (AI). One specific LSCI task is the synchronization of VSPs' digital replicas, i.e., the digital entities which mirror their real-world counterparts. To collect and process the counterparts' state data for the synchronization, flexible Internet-of-Things (IoT) devices and advanced computation methods with reduced latency at the network edge are necessary. In particular, the advanced computation method can be considered a service provided by edge infrastructure providers (EIPs) that offer edge computing services to IoT devices so as to avoid a long transmission delay in the backhaul. Since different VSPs may have different synchronization preferences for their digital replicas based on their service types, an effective synchronization solution should consider various agents, i.e., IoT devices, EIPs, and VSPs. In this thesis, I aim to study their strategic interactions using game-theoretical approaches, in the context of (1) VSPs' synchronization assisted by ubiquitous IoT devices in chapter3 and (2) advanced computation services offered by EIPs to facilitate LSCI tasks in chapter4.